Chest reconstructive surgeries in transmasculine youth: Experience from one pediatric center. Issue 4 (2nd October 2017) - Marinkovic, Maja; Newfield, Ron S.
ABSTRACT: Background : For many trans males, having chest reconstruction is a very important part of the transitioning process. Guidelines from WPATH and the Endocrine Society suggest 16 to 18 years old as an acceptable age for this surgical intervention. In clinical practice, the decision depends on factors such as a person's desires, insurance coverage, and availability of local surgical experts. We present data about chest reconstructive surgeries in transgender youth from a Pediatric Gender Management (GeM) clinic. Methods : For this retrospective, observational study, data were collected from GeM clinic patients seen from 10/1/2011 to 1/31/2017. All subjects consented or assented to being included in an IRB-approved clinical database. Results : Of 210 patients from our clinic, 167 consented to being added to an institutional review board–approved database and followed prospectively. The average age at the initial visit was 15.2 years (range, 4.7–20.9). Among consenting subjects, 55 were trans females, 108 were trans males, and four identified as nonbinary. Fourteen subjects had chest reconstruction with the mean age being 17.2 years (range, 13.4–19.7); three subjects were under age 16. For five subjects, including the youngest one, insurance paid for the procedure. All participants but one were receiving testosterone treatment. Per the surgeons' preferences, testosterone was usually not temporarily stopped prior to the procedure. Six subjects had the procedure done locally; others sought surgical care out of the town, state, or country. All subjects were very satisfied with the aesthetics of the surgical outcome. The self-reported complication rate was low. Many more GeM clinic patients wish to have breast/chest surgery but lack of insurance coverage makes the surgery cost prohibitive. Conclusion : For many trans males, chest reconstructive surgery is an integral part of the transition process. Patients' age at the time of surgical procedure varies greatly; some have chest surgery before age 16. In the United States, chest reconstruction surgery is usually not covered by insurance. Therefore, many patients seeking surgical care are forced to pay out of pocket.